The Socio-Historical Construction of the “Social Risk” Notion. Intervention, Legislation and Institutionsin Costa Rica (1821-1880) - Izquierdo Vázquez, Carlos (2022)
The article analyzes how care was developed for various poor sectors in Costa Rica. Through the review of laws, decrees and official circulars, it is shown that the State practiced different protection measures through the early institutionalization of charity, the partial or total exoneration of certain charges, the distribution of land and the promotion of public health through medicine and hospitals. Various actors were key in its development, such as citizens, the Catholic Church and some members of the elites. Its purposes were also the strengthening of capitalism, the promotion of the agricultural production and the fight against vagrancy. It is concluded that the State was institutionalizing charity and public health towards poor populations through the financing and supervision of various actors.